PENGARUH PRESTASI BELAJAR DAN DUKUNGAN ORANG TUA TERHADAP MOTIVASI KULIAH SISWA SMKN 1 DLANGGU MOJOKERTO - Dewi Shafira, Jasmine Izza; Hidayatun Muyasyaroh; Luthfiyah Nurlaela; Febriani Lukitasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The percentage of graduates from the Culinary Arts Program at SMK Negeri 1 Dlanggu, Mojokerto, who continue their education at the university level remains relatively low (10.59% of 255 graduates), indicating variations in motivation to pursue further education that are likely influenced by academic achievement and parental support. This study aims to determine the effect of academic achievement and parental support on students’ motivation to continue their education at the university level, both partially and simultaneously. The study used a quantitative approach with a survey method involving 60 11th-grade Culinary Arts students selected through purposive sampling. Data were collected via a Likert-scale questionnaire and analyzed using multiple linear regression, t-tests, and F-tests. The results showed that academic achievement had a positive and significant partial effect, while parental support was not significant when considered partially. However, both factors had a significant simultaneous effect, contributing 24.3% to the variation in students’ motivation. Students’ motivation to continue their college education is shaped by the interaction between their learning ability and family support combined